Identification of the different salivary Interleukin-6 profiles in patients with periodontitis: A cross-sectional study - Isola, Gaetano; Lo Giudice, Antonino; Polizzi, Alessandro; Alibrandi, Angela; Murabito, Paolo; Indelicato, Francesco (Archives of oral biology, 2021)
•PT patients had significant higher serum and salivary IL-6.•There was a significant progressive increase in salivary IL-6 with a proportional extent level of PT and tooth loss.•Salivary IL-6 was demonstrated a valid salivary predictor of gingival health. The aim of this study was to analyze and identify the association among salivary interleukin-6 (IL-6) levels and periodontitis (PT) and to determine the significant trend of this association in PT patients. For the present study, 49 patients with PT and 47 healthy subjects (HS) were enrolled and assessed for clinical parameters, blood samples and salivary IL-6 analyses. Clinical differences among groups were recorded and evaluated. The Spearman Correlation and the Jonckheere-Terpstra Test were applied in order to assess the interdependence between salivary IL-6 and PT. Patients in the PT group had significantly higher median salivary IL-6 levels [195.4 (184.6–205.9 pg/mL)] compared to the HS group [101.9 (89.5–115.4 pg/mL) (p < 0.001). Salivary IL-6 levels were negatively correlated with C-reactive protein, with the number of teeth and with clinical attachment loss (CAL), probing pocket depth (PPD), and bleeding sites (FMBS) (p < 0.001). Furthermore, in patients with PT, salivary IL-6 levels were inversely associated (P-trend) with the number of teeth (p < 0.001), and directly associated with the proportional extent of PT (CAL, p = 0.006; PPD, p = 0.009; FMBS, p < 0.001). The results of this study showed that PT patients presented significant higher salivary IL-6 levels compared to HS. Moreover, in the analyzed sample a significant p-trend among PT, tooth loss and increased salivary IL-6 levels was found.